Proses Penyitaan Barang Bukti Dalam Tindak Pidana Narkotika - I Kadek Sudikma; I Ketut Sukadana; I Nyoman Gede Sugiartha (Jurnal Preferensi Hukum, 2020)
The police force is a government agency that has the authority to conduct foreclosures. Foreclosures that are carried out must meet elements of a criminal offense. One example of confiscation carried out by the Police is confiscation carried out in the case of abuse of Narcotics. The purpose of this study is to describe the regulation of criminal law against narcotics crimes and to determine the authority of investigators in confiscating narcotics evidence and the process of confiscating narcotics evidence. The method used in this study is normative with a legislative approach that is relevant to the problem under study. The source of legal material used is library research or library research. After the legal materials are collected, they are analyzed qualitatively. The results of this study indicate that confiscation of evidence is a stage that is carried out is very determining the existence of a criminal act or not. If the evidence to determine the existence of a crime is very appropriate, then the evidence can be used to support other evidence. The process of confiscating evidence of narcotics crime can be carried out in four types of foreclosure, namely: Ordinary confiscation, Confiscation in a state of emergency, Confiscation of caught hands, Confiscation of Letters or other writings.